Marfan syndrome, inherited aortopathies and exercise: What is the right answer?. Issue 2 (4th January 2016) - Cheng, Andrew; Owens, David
Abstract : Exercise recommendations for those who have Marfan syndrome or other genetic predisposition for thoracic aortic disease remain controversial and at times ambiguous. There are no outcomes studies to help guide recommendations. In this review, we examine the guidelines regarding exercise and inherited aortic conditions, the theoretical reasoning and circumstantial evidence that support the guidelines, as well as the knowledge gaps that continue to exist.